Emulsion-alginate beads designed to control in vitro intestinal lipolysis: Towards appetite control - Meinou N. Corstens (Journal of Functional Foods, 2017)
Dietary lipids and digestion products are strong inducers of satiety signals in the distal small intestine. To protect lipids against proximal absorption we encapsulate them in hydrogel beads. Physically stable beads of different sizes (0.55, 0.78 and 1.15 mm), and mesh sizes (ξ = 9.2, 6.4 and 5.4 nm) were obtained using ionotropic (Ca) gelation of alginate containing oil-in-water (O/W) emulsions (d32 ∼ 21 μm). All beads shrunk at pH 2.0, and had excellent gastric stability (2 h, pepsin, pH 3.0), while they swelled at pH 7.0, and softened under simulated intestinal conditions (2.5 h, pancreatin, bile, pH 7.0). Lipolysis could be controlled through variation of bead and mesh size, resulting in a broad range of release profiles: from 1–50% release after 1 h to 20–80% after 2.5 h. Such systems with controllable and predictable in vitro release profiles are a promising step towards ileal lipid release, where they could play a pivotal role in appetite control.